Universidade Livre Feminista : uma abordagem em favor do protagonismo social das mulheres pautada nas dimensões da mediação consciente da informação - Oliveira, Joelma da Silva (2023)
The present research aims to discuss the social empowerment of women through the mediation of information provided to female participants in the educational process implemented by the Free Feminist University (ULF). By addressing the concepts of information, information mediation, and women's social empowerment, it argues for the presence of dimensions of information mediation - dialogical, formative, aesthetic, ethical, and political – in the educational process carried out by ULF, engaging with the consequences of the historical oppressions faced by women as subjects of interactions, but also of subordination to capitalist, sexist, and racist structures. Social empowerment, as a concept whose relational meaning can be understood in the individual and collective aspects of individuals involved in a specific context, is seen as a condition of women's empowerment. The research problem is based on how information mediation influences the social empowerment of women participating in the training process promoted by ULF. Considering that these women share a common reality by being linked to feminist groups or organizations, the research question is: How can ULF contribute to strengthening women's social empowerment through conscious information mediation? We assume that the Free Feminist University has a significant contribution to society, especially by enabling access to and appropriation of information with a view to social empowerment. The general objective was to analyze the information mediation outlined by the Free Feminist University as a strategy that favors women's social empowerment through its different dimensions. The specific objectives were: 1) to describe the process of conscious information mediation outlined by the Free Feminist University, developed through Digital Communication Technologies; 2) to present the contents of the training process of the Free Feminist University in connection with the dimensions of mediation; and 3) to assess how female participants in the training courses appropriate the information mediated by the Free Feminist University, contributing to the achievement of social empowerment. The research conducted is correlational with a qualitative approach. The research analysis method consists of Content Analysis (CA). A total of 15 questionnaires were applied, answered by the respondents who participated in the courses held between 2018 and 2021, of which 10 were analyzed. Additionally, five in-depth interviews were conducted. The results confirm that ULF's information mediation achieves the realization of the five dimensions: dialogical, formative, aesthetic, ethical, and political, through the training accessed by women who appropriate the disseminated content. It was concluded that the mediated contents in the training sessions evidence the appropriation of information, contributing to women's social empowerment.